Seasonal hydrological and hydrochemical surveys in the Voevoda Bay (Amur Bay, Japan Sea) - Yury A. Barabanshchikov; Pavel Ya. Tishchenko; Pavel Yu. Semkin; Tamara I. Volkova; Vladimir I. Zvalinsky; Tatyana A. Mikhailik; Sergey G. Sagalaev; Aleksandr F. Sergeev; Petr P. Tishchenko; Maria G. Shvetsova; Elena M. Shkirnikova (Известия ТИНРО, 2015)
Hydrological and hydrochemical surveys were conducted in the Voevoda Bay in May, August, and October, 2011 and February, 2012, in total 140 stations. Free water exchange of the bay with the Amur Bay is observed, with exception of its inner bights Kruglaya and Melkovodnaya. The water exchange is maintained by anticyclonic circulation with the inflow along the southern coast and outflow along the northern coast of the Voyevoda Bay. However, the opposite cyclonic circulation is observed in the Melkovodanaya Bight because of its coastal line patterns and fresh water discharge by the river. Dissolved oxygen content and partial pressure of CO2 in the bay waters are determined mostly by intensive processes of production and destruction of organic matter. There are three main groups of primary producers there, as diatom algae, sea grass Zostera marina , and periphyton. Specific chemical regime is formed in the Melkovodnaya Bight, in particular in winter when primary production depends on the ice cover and is driven by variations of photosynthetically active radiation passed through the ice. Seasonal variability of production-destruction processes intensity is discussed on the data of chemical parameters changes.